Design guidelines of a rainwater harvesting and rainwater treatment system for DOST NCR office - David, Paolo B.
The mam purpose of this study is to design a set of guidelines for a rainwater harvesting and rainwater treatment facility for DOST NCR Office. This study aims to design each component of a suitable rainwater harvesting and treatment facility that is vital for supplementing the estimated water demand of DOST NCR Office. In the study, the main components of a rainwater harvesting and rainwater treatment system were studied and analyzed for the design for DOST NCR Office. These components are the roof catchment area, the conveyance system, rainwater storage tanks, and the rainwater treatment technique of slow sand filtration. In making the design of the facility, simulations were preformed in order to produce a reliability curve, which will be used to identify how efficient a specific storage tank size for a given set of parameters will be suitable for the system. Identifying this will guide the design for the specifications needed for the rainwater harvesting and rainwater treatment facility. A storage tank size for the facility and a configuration for the slow sand filter for rainwater treatment are then recommended based from the analysis of the study. A design manual is then drafted with the purpose to be used as a guide in commissioning the facility for DOST NCR Office.